КОМПОНЕНТЫ СТРУКТУРЫ ТЕХНИЧЕСКОЙ ПОДГОТОВКИ АКРОБАТОВ - Умаров, Х.Х. (SCIENCE and SOCIETY, 2022)
The presented article reveals the basics of technical training of acrobats. The structure of motor action of sportsmen, "school" of movements is substantiated. The significance of "special technical training" in the general system of training young acrobats - jumpers, the direction of improving the technique of competitive exercises by years of study is determined.
Keywords: technical training; "school" of movements; coordination of movements; artistry; statistics; biomechanics of movements